Reduced circulating regulatory T cells in primary Sjögren’s syndrome: the contribution of enhanced apoptosis and impaired survival - Wang, Yanlin; Jia, Yuhan; Guo, Hui; Feng, Min; Qin, Yan; Liang, Zhaojun; Zhao, Xiangcong; Gao, Chong; Luo, Jing (Frontiers in Immunology, 2025)
BackgroundRegulatory T cells (Tregs) are found to be critical for maintaining immune tolerance to self-antigens; however, their status in primary Sjögren’s syndrome (pSS) remains unclear. We investigated alterations in the abundance of peripheral Tregs in a large pSS cohort and their implications for patients.MethodsLevels of CD4+CD25+FOXP3+Treg cells in the peripheral blood of 624 patients with pSS, and 93 healthy controls (HCs) were detected using modified flow cytometry (FCM). We then performed transcriptome sequencing of CD4+CD25+CD127-Treg cells, and used droplet digital PCR (ddPCR) to validate that the apoptosis-related genes were found in the sorted Treg cells. Apoptosis of CD4+CD25+CD127-Treg cells was verified using 7-AAD and annexin-V staining. We performed FOXP3/activated caspase-3 double immunohistochemistry to characterize features of the labial salivary glands.ResultsThe peripheral abundance of Treg cells from relapsing pSS patients was significantly contracted, especially in patients with high disease activity. We identified 187 upregulated and 674 downregulated DEGs in sorted Tregs from pSS patients, including five apoptotic pathway hub genes (XIAP, CASP3, CASP10, NFKBIA, and PMAIP1)-a finding consistent with increased Treg apoptosis in pSS. Active caspase-3 was detected in FOXP3+ cells within the minor labial salivary gland tissue of pSS patients. Higher levels of active Caspase-3 were correlated with lower Treg cell numbers. Interestingly, although the downregulation of the PI3K/AKT signaling pathway did not reach statistical significance, this vital pro-survival axis may still contribute to Treg impairment in pSS.ConclusionsThese data suggest that the decreased peripheral abundance and increased apoptosis of Treg cells play an important role in the pathogenesis of pSS. Therefore, approaches for increasing Treg numbers in vivo could provide precise pSS therapy.